CREATIVE LIBRARY AS A CATALYST FOR STUDENTS' READING INTEREST IN KUNINGAN WEST JAVA - Intan Darmayanti; Erny Roesminingsih; Sri Setyowati; Amrozi Khamidi; Mohammad Syahidul Haq; Kaniati Amalia (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2025)
This study aims to analyze the role of creative libraries as catalysts for students' reading interest by highlighting innovations in space design, literacy activities, and appreciation systems in two public schools in Kuningan, West Java. This study uses a qualitative descriptive approach with a multi-site case study design, involving key informants, namely librarians, teachers, and students. This study was conducted over six months of field data collection through observation, in-depth interviews, and documentation. Different from previous school literacy studies that focused solely on reading activities, this study introduces the "Creative Library as an Interactive Ecosystem" model, which positions the reading space as a dynamic system that drives intrinsic motivation. The findings indicate four main innovations: (1) spatial arrangement based on comfort and visual aesthetics, (2) routine and collaborative literacy activities, (3) creative literacy communities such as book clubs and theater, and (4) an inclusive appreciation system that fosters a sense of achievement. Theoretically, this research updates the understanding of reading behavior by referring to the Integrative Framework of Motivation in Education (Urhahne & Wijnia, 2023) and the Holistic Design of Learning Environments (Barrett et al., 2019), which emphasize the importance of autonomy, competence, and social connectedness in learning ecosystems. Practically, the resulting catalyst model provides a new direction for school literacy policy in Indonesia, developing libraries as participatory, aesthetic, and socially meaningful spaces.